Peringati Hari Donor Sedunia PT SIER Mengumpulkan Ratusan Kantong Darah - Ramalio Fahridho Sakti; Nuruni Ika Kusumawardhani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
As blood is an essential part of the human body, the blood supply at the Indonesian Red Cross must be maintained. However, currently the amount of blood supply in the Indonesian Red Cross is decreasing. Seeing this situation, PT Surabaya Industrial Estate Rungkut (SIER) conducted a blood donor service activity to the community. The purpose of this activity is to provide education and socialization of the importance of blood donation, increase the number of blood bags at PMI Gunung Anyar and PMI Surabaya City, humanitarian efforts to help others, and prove community service as a form of social responsibility. The activity was carried out on June 24, 2024 at the SIER Clinic in Gunung Anyar District, Surabaya City, and still followed health protocols. The activity was attended by 101 people. The amount of blood collected was 101 bags. Overall, the event ran smoothly and orderly and it is hoped that the event will be a success.